Reused green glass for the production of low-density ceramic proppants - Anaya, Ricardo Javier (2024)
The reuse of waste to promote manufacturing processes that are respectful of the environment is a fundamental requirement in circular economy practices. In this work, it is assessed the feasibility of manufacturing ceramic proppants from a commercial red clay, sodium and potassium feldspars, and significant amounts of green bottle glass recovered from urban wastes.Different ceramic mixtures were formulated, and the sintering conditions were defined considering optical dilatometric, differential thermal, and thermogravimetric analysis. The obtained granules were characterised following the international standard for proppants, and also using X-ray diffraction, scanning electron microscopy, and individual diametral compression tests.The results show that competitive proppants are obtained, due to their low-density (2.5 g/cm3) and good breakage ratio (7.8 % at 5000 psi, or 34.5 MPa), but also considering the involved low-cost processing route and raw materials.